Setting up The Punchline In Conventional and Non-Conventional Pragmatics In Comedy Setups - Intan Ayu Sabrina (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2024)
This study investigates how conventional and non-conventional pragmatic strategies shape humor in comedic setups across various platforms such as stand-up comedy, sitcoms, and digital content. With the growth of digital media and the increasing diversity of comedic styles, understanding the use of pragmatic strategies in humor has become essential to grasping the social and cultural dynamics embedded in comedy. Using a qualitative discourse-pragmatic approach, the research applies Grice's Cooperative Principle as well as Incongruity and Relevance Theory to analyze how comedians construct and deliver humor. Data were collected through the analysis of transcripts from popular comedy shows and digital content to identify patterns in the use of pragmatic strategies. The findings reveal that conventional pragmatic strategies—such as presupposition and implicature—enhance audience relatability and accessibility by drawing on shared schemas and logical coherence. In contrast, non-conventional strategies—such as irony, hyperbole, and absurdity—flout conversational norms to trigger surprise and reinterpretation, often resonating more strongly in specific cultural or stylistic contexts. The study concludes that an effective comedic setup often results from a balance between adhering to and subverting pragmatic norms, allowing for both emotional connection and intellectual engagement. This research contributes to linguistic and humor studies by offering insights into how language use in comedy reflects broader social and cultural dynamics.